A new consumer price index that incorporates housing - Anders Klevmarken; Olle Grünewald; Henrik Allansson (Uppsala University, Department of Economics, 2009)
A long lasting controversy in Sweden as well as internationally is how to best estimate a price on the services of owner occupied housing in a consumer price index. There is no international consensus and different approaches have been adopted. In this paper we use a true cost-of-living index suggested by one of the authors, apply the model to Swedish data and compare the results to the current Swedish CPI. We also show that within the economic model underlying the true cost-of-living index, alternative operationalizations of the index give rather different results. The choice between these alternatives depends upon the primary purpose of the index.
urn:nbn:se:uu:diva-110596
Keywords: C43; D91; 330; price index; cost-of-living index; compensation index; price of housing services; Verbraucherpreisindex; Indexberechnung; Wohneigentum; Schweden